Obtención de aceite esencial de semilla de durazno por método soxhlet y arrastre de vapor (2019)
This work evaluated the obtaining of peach seed oil, the seed was obtained as waste in a company of natural juices and pulps. The oil was extracted using the Soxhlet and Steam Distillation The process variables were particle size, solvent type and extraction time, the response variable was yield. The design of experiments was carried out according to the previous bibliographic review, a solid ratio was established: liquid of 1:4 with extraction temperatures between 50-60°C for n-Hexane and 60-70°C for Ethanol. The best performance percentages of the Soxhlet method were 54% and 16.80% using n-Hexane and Ethanol respectively. With particle sizes of 0.425 mm and extraction time of 4 hours. As for the Steam Trawl method, the yields obtained were 17.19% and 9.04% using n-Hexane and Ethanol correspondingly, extracted with a particle size of 0.425 mm and an operating time of 2 hours. The physicochemical characterization of the highest performing sample revealed an iodine index of 97.75 g I/g, saponification index of 200.08 mg KOH/g, peroxide index of 23.64 meq/g, acidity index of 0.98 mg KOH/g, refractive index of 1.38 nD and density of 0.89 g/mL.